STS Between Centers and Peripheries: How Transnational are Leading STS Journals? - Invernizzi, Noela (2022)
In the context of increasing internationalization of the science and technology studies (STS) field, and reflections on post-coloniality and provincialization of STS, we examine to what extent a set of twelve leading journals of the field have published papers from different regions worldwide. In this exploratory work, based on information retrieved from the Web of Science for the period 2010–2019, we often use Latin America as an example, but reflect on peripheral regions of the field more broadly. Our findings show that the historical West-European–North-American centers of the field maintain their hegemony, dominating the discussions in leading journals. Some Latin American and East Asian countries gained some visibility in journals focused on scientometrics and science and technology (S&T) policy and innovation, whereas the journals specialized in the socio-anthropological studies of S&T are the less transnationalized. Our preliminary hypothesis to explain such sub-field variations is that these objects (scientific policy, innovation) and methods (scientometrics) seem to be more universal and consensual, facilitating transnationalization, while peripheral science, the preferred object of study for peripheral STS, has not attracted attention from leading journals. Emphasizing the relational character of centers and peripheries, we argue that the invisibilization of the academic production of certain regions of the world in leading journals makes this work peripheral.